Influencia del Cáncer en el Estado Emocional del Paciente y su Familia - Abad Tacuri, Maritza del Cisne (2016)
The follow research has been done to the cancer patients and their families attending at MANUEL IGNACIO MONTERO hospital (IESS) from Loja city, focused on analyze the problems caused by cancer as the emotional impact and the low family’s participation in the treatment Currently, cancer patients like other chronic patients suffer effects that afflicts them on the emotional, social, economic and household level, the concept of quality of life is analyzed from a multidimensional perspective, which aims to show the level of physical , psychological and social related to the disease and treatment (Saleeba, 1996), which means taking into account the idiosyncrasies of each individual, their culture, perception (highly subjective) of the disease evolution and prognosis. The follow problem called “how is the influence in the emotional state of the patient at MANUEL IGNACIO MONTERO hospital” that allows to know the reality of patients and their families attending the nursing home, To carry out the research, involved the fieldwork, with the support of a broad theoretical content - scientist allowed support and explain categories of analysis such as: cancer as a disease, cancer and its treatment, palliative care, definition of families, patient's emotional state, emotional state of the family and social work in health. To comply with the research problem, it was formulated the general objective revolves around determining the level of family involvement in the oncological treatment of people with cancer at Manuel Ignacio Montero 6 hospital, through the application of instruments that allowed know the reality experienced by patients and their families attending medical consultations for appropriate treatment; Specific objectives which are summarized as: Sustain theoretically categories of problem under study, for information and important aspects of this social problem; The second objective is to determine how it affects cancer disease in the emotional state of the patient and family through the application of tools, and finally the third objective is to design a proposal for social intervention with the family to strengthen their participation in the treatment of cancer patients. This research could identify factors: economic, hometowns work-occupation significantly affect for family members not involved in the treatment process, which creates a great emotional distress in cancer patients. Another finding in the research is that women are more affected with breast cancer; this creates a physical change in your body which creates a great depression and low self-esteem because of their physical change. For the investigative process was used the Insertion Methodology Reality with its phases and levels, as the survey instrument and unstructured interview with our 42 cancer patients and 35 family members attending the hospital was used for this research process. Therefore it is concluded and recommended that it is necessary to create a proposal for a social action targeted at promoting and raising awareness of the importance of the family in the treatment process 7 diagnosis, in this way reduce the emotional impact from disease and improve quality of life each patient.